Structural survey of old reinforced concrete elevated water tanks in an earthquake-prone area. (1st May 2021) - Dilena, Michele; Dell'Oste, Marta Fedele; Gubana, Alessandra; Morassi, Antonino; Polentarutti, Francesco; Puntel, Eric
Highlights: In situ investigation of old concrete water tanks in an earthquake prone region. Defect detection, mechanical characterization of concrete and steel, soil testing. Detailing reconstruction. Dynamic testing under environmental excitation. Finite element analyses and comparison with experimental data. Abstract: Water tanks are elements of strategic infrastructure in the context of major earthquakes and must be assessed to determine their conditions. A reliable collection of experimental data is particularly important before any assessment procedure. This research theme has been deeply investigated for buildings; however, relatively less data is available regarding existing water tanks. In this study, the methodology and results from a survey of water tanks managed by a water utility in north-eastern Italy are presented. A fairly large sample of twelve water tanks (representative of different typologies) was analysed. The water tanks were built in an earthquake-prone region approximately 60 years ago, when no seismic provisions were enacted. A systematic in situ experimental campaign was at the core of the proposed approach; it encompassed concrete and steel and employed both destructive and non-destructive tests. In addition, a structural dynamic characterisation was performed. The purpose of these investigations was to collect experimental data for building reliable finite element models (as required for subsequent seismic structural assessments), and for the planning of future retrofitting interventions. The present work aims to act as both a methodological reference and a source of useful experimental data for structures of similar age and typology.